Sepsise ja septilise šoki ravijuhend 2018 – esmane diagnostika ja ravivõtted - Karu, Inga; Tamme, Kadri; Mitt, Piret; Keskpaik, Triinu; Starkopf, Joel (Eesti Arst, 2018)
Eesti Arst 2018; 97(7):387–392